ANALISIS KESUKAAN TERHADAP KARAKTERISTIK OLAHAN NUGGET YANG DISUBTITUSI DENGAN RUMPUT LAUT DAN TEPUNG SAGU - Syamsuddin, Nurfadilah; Lahming, Lahming; Caronge, Muhammad Wiharto (Universitas Negeri Makassar, 2015)
This research aim to determine the level of preference to the characteristic (texture, flavour, color and aroma) in nugget that subtitued with a seaweed (Kappaphycus alvarezii) and sago flour. Type of this research is a quantitative research with experimental approaches using a completely randomized factorial design consist of two factors, namely factor A is seaweed (control, 200g, 300g, 400g) and factor B is sago flour (control, 15%, 25%, 35%). All the treatments was tested as 16 treatment combinations. Each treatment combinations was repeated4 times that obtain 64 units experiment. The data of this research was obtained from the result of organoleptic characteristics test using hedonic scale scoring method. The results of this research showed the most preferred texture obtained in the treatment combination A2B4isformulation of 200g seaweed and use 35% of sago flour, the most preferred flavour obtained in the treatment combination A1B1is formulation of chicken meat with maizena flour or nugget control, the most preferred color acquired in the treatment combination A1B2isformulation 200g of chicken meat with substitued 15% of sago flour and the most preferred aroma obtained in the treatment combination A2B4 is formulation of 200g seaweed with substituted 35% of sago flour